2022
DOI: 10.3390/ijms232012613
|View full text |Cite
|
Sign up to set email alerts
|

Polysiloxane-Based Polyurethanes with High Strength and Recyclability

Abstract: Polysiloxanes have attracted considerable attention in biomedical engineering, owing to their inherent properties, including good flexibility and biocompatibility. However, their low mechanical strength limits their application scope. In this study, we synthesized a polysiloxane-based polyurethane by chemical copolymerization. A series of thermoplastic polysiloxane-polyurethanes (Si-TPUs) was synthesized using hydroxyl-terminated polydimethylsiloxane containing two carbamate groups at the tail of the polymer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The pristine microstructure foil had a contact angle of 109°, the plasma-treated PDMS foil exhibited a contact angle of 24°, and the plasma-treated PDMS microstructure with collagen had a contact angle of 54°; these results are also in good agreement with Keffalinou et al [ 90 ]. Wettability-patterned surfaces prepared by an Atmospheric-Pressure Plasma Jet were used in microfluidic devices [ 91 ], and wettability also has a significant impact on microchannels in enhancing droplet coalescence and demulsification [ 92 ] and surface activation of polymer blends for recyclability [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pristine microstructure foil had a contact angle of 109°, the plasma-treated PDMS foil exhibited a contact angle of 24°, and the plasma-treated PDMS microstructure with collagen had a contact angle of 54°; these results are also in good agreement with Keffalinou et al [ 90 ]. Wettability-patterned surfaces prepared by an Atmospheric-Pressure Plasma Jet were used in microfluidic devices [ 91 ], and wettability also has a significant impact on microchannels in enhancing droplet coalescence and demulsification [ 92 ] and surface activation of polymer blends for recyclability [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the surface C/O ratio was almost two times higher than the volume ratio for both the initial PU and the composites. In principle, surface segregation in PUs is a well-known phenomenon (for example, see [ 23 , 24 , 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 ]). In the case of our study, the surface C/N ratio changed symbatically with the change in the GO concentration, while the volume ratio remained almost constant ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Silicone polymers have lower intermolecular forces, so an excessive amount of silicone can reduce the mechanical strength of the material, consistent with our surface analysis results. Additionally, an excess of silicone may reduce material compatibility, thereby affecting its phase separation and, consequently, 29 its mechanical performance.…”
Section: Discussionmentioning
confidence: 99%